2011
DOI: 10.2528/pierm10121503
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Approximate Formulas for Internal Impedance of Tubular Cylindrical Conductors for Large Parameters

Abstract: Abstract-Exact formulas for internal impedance per unit length of tubular cylindrical conductors energized by time-harmonic current involve Bessel functions. These functions are defined by infinite series, which yield unstable and often erroneous results for complex arguments of large magnitudes. Although it is well known how to evaluate Bessel functions numerically and many routines are now available to perform the actual computation, the available software routines often fail when computing equations that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…It can be shown that in the DC limit → 0 the imaginary part of the bracket converges to −1/4, so that log( ) adopts its DC value given by equation (17), as expected. The total inductance of a finitely long round wire at arbitrary frequency can be approximated by equation (7) with log( ) given by equation (30), or by its approximate formula (38) based on elementary functions taken from paragraph 6.3.3.…”
Section: Derivation Of the Gmdsupporting
confidence: 73%
See 3 more Smart Citations
“…It can be shown that in the DC limit → 0 the imaginary part of the bracket converges to −1/4, so that log( ) adopts its DC value given by equation (17), as expected. The total inductance of a finitely long round wire at arbitrary frequency can be approximated by equation (7) with log( ) given by equation (30), or by its approximate formula (38) based on elementary functions taken from paragraph 6.3.3.…”
Section: Derivation Of the Gmdsupporting
confidence: 73%
“…In the limit → 0 this reduces to the constant −1/4, thus reproducing the GMD of a circular disk as given by equation (17). Inserting equation (22) into (7) yields Wiens's formula for the DC inductance of a tubular conductor of finite length ( [9], p. 938).…”
Section: Tubular Conductor At DCmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, the interest in circular and tubular geometries has apparently rebirth [10][11][12][13][14][15][16][17][18][19][20][21], however, most of published work has been focused on the development of approximate formulas for internal impedance evaluation of homogeneous structures. Those formulas are basically used to circumvent the troublesome computation of Bessel functions.…”
Section: Introductionmentioning
confidence: 99%